2018
DOI: 10.3892/mco.2018.1649
|View full text |Cite
|
Sign up to set email alerts
|

Management of MANEC of the colon and rectum: A comprehensive review of the literature

Abstract: Mixed adeno-neuroendocrine carcinoma (MANEC) is a rare pathological diagnosis recently acknowledged by the World Health Organization in 2010. MANEC is a neoplasm characterized by significant histological heterogeneity and is characterized by the simultaneous presence of both adenocarcinomatous and neuroendocrine differentiation; their definition includes each component found in at least 30% of the tumor. Colorectal MANEC constitutes an uncommon type of malignant tumor. The true prevalence of colorectal MANEC h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 18 publications
(20 reference statements)
0
48
0
Order By: Relevance
“…Moreover, these tumors could be detected at advanced stage[3]. The 3-year overall survival (OS) was estimated to be 5%–27%[1,4,5], and response to chemotherapy was reported as the only predictive factor in patients with metastasis[1]. Because of its aggressive nature and high recurrence rate of the NEC, adjuvant chemotherapy constitutes a critical part of the treatment and significantly improves survival[4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these tumors could be detected at advanced stage[3]. The 3-year overall survival (OS) was estimated to be 5%–27%[1,4,5], and response to chemotherapy was reported as the only predictive factor in patients with metastasis[1]. Because of its aggressive nature and high recurrence rate of the NEC, adjuvant chemotherapy constitutes a critical part of the treatment and significantly improves survival[4].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, others support the hypothesis of both morphologically distinctive carcinomas arising from a common, multipotent stem or progenitor cell (16). As far as the histology of these rare tumors is concerned, interesting findings have been observed (8,29). Features of ordinary adenocarcinoma are usually recognized in the tumor surface, the neuroendocrine component has been recognized in areas of vascular and perineural infiltration, while neuroendocrine components were prominent in lymph node involvement cases (29).…”
Section: Discussionmentioning
confidence: 95%
“…It is acknowledged that long-term outcomes in these patients are largely dependent on the most aggressive component (adenocarcinoma/NEC) of their tumor (8,31,32). Long-term outcomes for patients with gallbladder neuroendocrine tumors have been shown to vary highly possibly due to their divergent disease stage and differentiation degree; 5-year survival rates range from approximately 37% to 60% (17,33) whereas the addition of the adenocarinomatous component is thought to dictate worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the latest and largest Western study reported very poor survival rates of localized gastric MANEC [35]. In some studies of colorectal carcinomas, a poorer prognosis was observed in patients with tumors that harbored chromogranin-positive cells [36, 37, 38, 39], but in other studies, this outcome was not confirmed [40, 41, 42, 43, 44]. Currently, there is no consensus regarding the prognostic significance of NE cells after neoadjuvant chemotherapy, and more studies are needed.…”
Section: Discussionmentioning
confidence: 99%